When it rains, it pours? Analyzing the rainfall shocks- poverty Nexus in the Philippines - Connie Bayudan-Dacuycuy; Lora Kryz Baje (Philippine Institute for Development Studies (PIDS), 2018)
Weather is an integral part of our life and weather shocks can have severe implications on welfare. Given the evidence that points to climate change resulting in altered patterns of weather parameters and given that the Philippines is one of the most vulnerable countries to climatic shifts, this paper aims to contribute to poverty studies in the Philippines by analyzing the poverty-rainfall shock nexus. The paper finds that rainfall shocks affect wages and income, which in turn, affect chronic total and chronic food poverty. Given that LGUs are in the forefront of the country's fight against the adverse effects of climate change, some policy directions are forwarded so that LGUs can better address issues on climate change. These include the development of climate-smart agriculture and the tapping of additional funding sources for projects on climate change adaptation. Partly due to exclusion errors, there are deserving households that are not part of the 4Ps. Suggestions are forwarded not only to improve the 4Ps' data management to accommodate vertical scale-up but to ensure that the program covers deserving beneficiaries as well. Policy directions on the development of adaptive social protection are also forwarded.
Keywords: 330; rainfall shock; components approach; chronic poverty; transient poverty; Philippines